Pengaruh Kepemimpinan Transaksional Budaya Organisasi Dan Perilaku Inovatif Terhadap Kinerja Karyawan (Studi Pada Perusahaan Anda Jaya Situbondo) - Haq, Moh. Izzul; Sudaryanti, Dwiyani; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study is to examine and elucidate the relationship between employee performance at Anda Jaya Company in Situbondo and transactional leadership, organizational culture, and innovative behavior. 33 respondents were chosen for the study sample using the saturation sampling technique. Multiple linear regression analysis was used to analyze quantitative data. Partial t-test was employed for hypothesis testing. The findings indicated that, at least in part, innovative behavior has a significant negative impact on employee performance in the company, organizational culture has a significant negative impact on employee performance, and transactional leadership has a significant positive impact. Keywords : Transactional Leadership, Organizational Culture, Innovative Behavior, and Employee Performance